2016
DOI: 10.1186/s13229-016-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Name recognition in autism: EEG evidence of altered patterns of brain activity and connectivity

Abstract: BackgroundImpaired orienting to social stimuli is one of the core early symptoms of autism spectrum disorder (ASD). However, in contrast to faces, name processing has rarely been studied in individuals with ASD. Here, we investigated brain activity and functional connectivity associated with recognition of names in the high-functioning ASD group and in the control group.MethodsEEG was recorded in 15 young males with ASD and 15 matched one-to-one control individuals. EEG data were analyzed with the event-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 103 publications
(139 reference statements)
3
40
2
Order By: Relevance
“…Evidence of decreased FNs to salient speech also resembles prior work showing similarly decreased late-latency FN response in ASD-MLV children when processing speech, albeit during a semantic congruence task [Cantiani et al, 2016;DiStefano et al, 2019]. However, our findings differ from prior reports in that we only identify significant differences with the FN component and not the LPP component [Nijhof et al, 2018;Nowicka, Cygan, Tacikowski, Ostaszewski, & Ku s, 2016;Tacikowski et al, 2014]. Future research is needed to better understand how the processes underlying these slow late positive and negative shifts evoked by OON interact and how differences in their neural morphology reflect underlying differences in higher-level auditory attention or selfreferential processing in ASD and TD samples.…”
Section: Late Attentional Orienting Responses To Oon and Their Associsupporting
confidence: 64%
“…Evidence of decreased FNs to salient speech also resembles prior work showing similarly decreased late-latency FN response in ASD-MLV children when processing speech, albeit during a semantic congruence task [Cantiani et al, 2016;DiStefano et al, 2019]. However, our findings differ from prior reports in that we only identify significant differences with the FN component and not the LPP component [Nijhof et al, 2018;Nowicka, Cygan, Tacikowski, Ostaszewski, & Ku s, 2016;Tacikowski et al, 2014]. Future research is needed to better understand how the processes underlying these slow late positive and negative shifts evoked by OON interact and how differences in their neural morphology reflect underlying differences in higher-level auditory attention or selfreferential processing in ASD and TD samples.…”
Section: Late Attentional Orienting Responses To Oon and Their Associsupporting
confidence: 64%
“…While we cannot compare our findings with other studies that have evaluated ERPs elicited by hearing the own name in ASD because our study is the first to investigate this phenomenon in ASD, it is worth comparing our results to the findings of two recent studies investigating ERPs in response to seeing the own name in ASD (Cygan et al, 2014;Nowicka et al, 2016). These studies reported, similar to what we found, enlarged amplitudes of a late parietal positivity (P300) for the own name versus other names in controls, and a lack of this modulation in individuals with ASD.…”
Section: Discussionmentioning
confidence: 77%
“…These results are in conformity with a previous study that reported deficits in sensory processing and selective‐attention tasks in visual and auditory areas (Verbaten et al, 1991). Another research group examined the self‐preference effect in ASD with the aid of P300 component (Nowicka et al, 2016). The visual stimuli consisted of four categories of names: one's own, close‐other's, famous and unknown.…”
Section: Methodologiesmentioning
confidence: 99%
“…With growing number of research into exploring brain connectivity, DTF has emerged as an efficient tool in casual interactions. An EEG study on males with ASD and control subjects was carried out to investigate the task-related brain connectivity during name processing (Nowicka et al, 2016). The DTF values were lesser in anterior-posterior region and higher within parietal-occipital region in ASD group compared to control participants.…”
Section: Asd Studies Based On Frequency Domain Measuresmentioning
confidence: 99%